A floating-point analog-to-digital converter - Shen, Shumin (University of Ottawa (Canada), 2004)
This thesis studies the floating-point analog-to-digital converter (FP-ADC). The first attempt is to analyze the parallel architecture of the floating-point converter, which is our research base. The characteristics and specifications of the floating-point AID converter are described. Simulations of the parallel architecture of the floating-point A/D converter were conceived, run and presented here to support the theoretically derived FP-ADC transfer characteristics. After analyzing the parallel architecture of the floating-point A/D converter, the following work is to provide a way of minimizing the conversion time as well as keeping the precision of the floating point A/D converter (FP-ADC) by implementing the parallel architecture with Field Programmable Gate Arrays (FPGA). The thesis presents the design and practical implementation of the parallel FP-ADC, based on a FPGA and other hybrid components-of-the-shelf. The correctness of the design was verified by computer simulation, while the functionality of the implemented FP-ADC was tested on a test bench controlled by a PC. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.